Delmar's case study series : medical-surgical nursing - Ankner, Gina M. (Clifton Park, New York : Delmar Cengage Learning, 2012)
'Medical-Surgical Nursing' bridges the gap between content knowledge and clinical application. Presented is a collection of 20 provocative real-life case scenarios, each with a range of different variables to consider.
The cardiovascular system & the blood -- The respiratory system -- The nervous/neurological system -- The integumentary system -- The digestive system -- The hepatobiliary system -- The urinary system -- The endocrine/metabolic system -- The musculoskeletal system -- The reproductive system -- Concepts of disaster preparedness.
Includes bibliographical references and index.
Keywords: NURSING CASE STUDIES